Correlation between Hemoglobin Level, Attention and Working Memory Scores - Jannatin Aliya Indrina; Anam Ong; Ihrul Prianza Prajitno (Faculty of Medicine Universitas Padjadjaran, 2014)
Background: Attention and working memory functions have important roles in daily activities. Normal level of hemoglobin is required for optimum attention and working memory functions. This study aims to analyze the correlation between hemoglobin level, attention, and working memory scores in medical students who attended Atlas Medical Pioneer (AMP) Basic Program XXI.Methods: The total population sample for this cross-sectional study included 27 males and 19 females. The hemoglobin level was meassured by using cyanmethemoglobin method. Digit Symbol Test, Digit Span Forward and Backward Test, Trail Making Test A and B, and Stroop Test were used to assess attention and working memory scores. The study was conducted from September to November 2012 in Jatinangor campus of the Faculty of Medicine, Universitas Padjadjaran and Clinical Pathology Laboratory of Dr. Hasan Sadikin General Hospital. The correlation analysis was performed using computer.Results: The correlation between hemoglobin level in males and attention on Trail Making Test A score was (r=0.144) (p=0.474). While the correlations with theTrail-Making Test B and Stroop Test scores were (r=0.332) (0.091), and (r=-0.320) (p=-0.103), respectively. For females, the correlations with the Trail Making Test A, Trail Making Test B, and Stroop Test scores were (r=0.121) (p=0.622), (r=-0.232) (p=0.338), and (r=0.137) (p=0.576), respectively. Meanwhile, the correlation between hemoglobin level and the working memory on Digit Symbol Test, Digit Span Forward Test, and Digit Span Backward Test scores for-males were (r=0.256) (p=0.197), (r=0.419) (p=0.029), and (r=0.113) (p=0.576), respectively. For-females, the same correlations were (r=0.412) (p=0.080), (r=-0.299) (p=0.213), and (r=-0.028) (p=0.909), respectively. The only test that showed statistically significant result was Digit Span Forward Test in males.Conclusions: There is evident of weak correlation between hemoglobin level, attention, and working memory scores in medical students who attended AMP Basic Program XXI. This may be due to the confounding factors affecting attention and working memory as well as a small sample size. [AMJ.2014;1(1):1–5]Keywords: attention score, hemoglobin level, working memory scoreKorelasi antara Kadar Hemoglobin, Pencapaian Skor Atensi, dan Skor Memori KerjaLatar Belakang: Fungsi atensi dan memori kerja memiliki peranan penting dalam aktivitas sehari-hari. Kadar hemoglobin yang normal dibutuhkan untuk mencapai fungsi atensi dan memori kerja yang optimal. Penelitian bertujuan untuk menganalisis korelasi antara kadar hemoglobin, skor atensi, dan memori kerja pada mahasiswa kedokteran yang mengikuti Pendidikan Dasar XXI Atlas Medical Pioneer (AMP).Metode: Studi potong lintang dengan jumlah sampel 46 orang, terdiri atas 27 orang laki-laki dan 19 orang perempuan. Perhitungan kadar hemoglobin menggunakan metode cyanmethemoglobin. Digit Symbol Test, Digit Span Forward dan Backward Test, Trail Making Test A dan B, dan Stroop Test digunakan untuk menilai skor atensi dan memori kerja. Penelitian dilaksanakan dari bulan September–November 2012 di Kampus Fakultas Kedokteran Universitas Padjadjaran Jatinangor dan Laboratorium Patologi Klinik Rumah Sakit Dr. Hasan Sadikin. Analisis korelasi menggunakan komputer.Hasil: Korelasi antara kadar hemoglobin laki-laki dengan skor atensi pada Trail Making Test A (r=0,144) (p=0,474), Trail Making Test B (r=0,332) (0,091), dan Stroop Test (r=-0,320) (p=-0,103). Pada perempuan hasil Trail Making Test A (r=0,121) (p=0,622), Trail Making Test B (r=-0,232) (p=0,338), dan Stroop Test (r=0,137) (p=0,576). Hasil korelasi antara kadar hemoglobin laki-laki dengan skor memori kerja pada Digit Symbol Test (r=0,256) (p=0,197), Digit Span Forward Test (r=0,419) (p=0,029), dan-Digit Span Backward Test (r=0,113) (p=0,576). Pada perempuan hasil Digit Symbol Test (r=0,412) (p=0,080), Digit Span Forward Test (r=-0,299) (p=0,213), dan Digit Span Backward Test (r=-0,028) (p=0,909). Tes yang memiliki nilai signifikan hanya Digit Span Forward Test pada laki-laki.Simpulan: Terdapat korelasi lemah antara kadar hemoglobin, atensi, dan memori kerja pada mahasiswa yang mengikuti Pendidikan Dasar XXI AMP. Hal ini dapat terjadi karena confounding factor yang dapat memengaruhi atensi dan memori kerja seseorang serta jumlah sampel penelitian yang sedikit.Kata kunci: kadar hemoglobin, skor atensi, skor memori kerja DOI: dx.doi.org/10.15850/amj.v1n1.288